PENGARUH PROFITABILITAS, DEBT EQUITY RATIO, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Widayanti Widayanti; Djoko Kristianto; Bambang Widarno (Universitas Slamet Riyadi, 2020)
The purpose of this study was to know the effect of profitability, debt to equity ratio and firm size on earnings management in manufacturing companies in the basic industrial sector and chemical metal subsectors and the like that were listed on the Indonesia Stock Exchange in 2016-2018. This type of research is an empirical study. The data source used in this study is secondary data. The study population is manufacturing companies in the basic industrial sector and chemical metal subsectors and the like that are listed on companies on the Stock Exchange for the period of 2016-2018. The sampling technique used purposive sampling with a sample of 13 companies. Data collection techniques used documentation. Data analysis techniques used multiple linear regression. The results showed that profitability has a positive and significant effect on earnings management. Debt to equity ratio has a positive and significant effect on earnings management. The firm size has an effect but is not significant on earnings management.